Optimal bank capital requirements: What do the macroeconomic models say? - Adam Gulan; Esa Jokivuolle; Fabio Verona (Bank of Finland, 2022)
The optimal level of banks' capital requirements has been a key research topic since at least the introduction of the Basel rules in the late 1980s. In this paper, we review the literature, focusing on recent findings from quantitative structural macroeconomic models. While dynamic stochastic general equilibrium models capture second-round (general equilibrium) effects such as the feedback effects from macroeconomic outcomes back to financial intermediation and the dynamic evolution of the economy following regulatory changes, they suffer from tractability issues, including treatment of nonlinear effects, that typically force modeling simplifications. Additionally, studies tend to be concerned with determining the optimal level of fixed capital requirements. Only a handful offer estimates of the optimal size of the dynamic buffers. Since optimal dynamic macroprudential policies depend heavily on the nature of the underlying shocks, questions arise regarding the robustness and potential side effects of such plicies. Despite progress, the optimal level of bank capital requirements - in either fixed or dynamic form - remains largely an open research question.
urn:nbn:fi:bof-202204291175
Keywords: 330